2011
DOI: 10.3171/2010.11.peds10216
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and postoperative developmental attainment in patients with sagittal synostosis: 5-year follow-up

Abstract: Object The object of this study was to clarify whether improved developmental attainment following surgical correction of sagittal synostosis (SS), previously identified at initial postoperative assessment, is maintained at longer-term follow-up at 5 years of age. Methods The study involved 32 children with SS who underwent corrective surgery at a mean (± SD) age of 8.5 ± 7.25 months (range 2.8–39.9 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 7 publications
(8 reference statements)
2
33
0
1
Order By: Relevance
“…The current data are consistent with the literature and also with our earlier findings of specific areas of locomotor difficulty at younger ages (Bellew et al 4,5 ). These earlier data indicated that children with SS have significantly poorer gross locomotor function than the normal controls.…”
Section: Discussion Long-term Developmental Outcomesupporting
confidence: 93%
“…The current data are consistent with the literature and also with our earlier findings of specific areas of locomotor difficulty at younger ages (Bellew et al 4,5 ). These earlier data indicated that children with SS have significantly poorer gross locomotor function than the normal controls.…”
Section: Discussion Long-term Developmental Outcomesupporting
confidence: 93%
“…Given the mixed findings from previous studies, 4,6,9,12,13,15,23,34,41,48 the primary aim of this investigation was to determine whether school-age children with SSC, all of whom underwent cranioplasty, have deficits in language and memory skills in relation to demographically similar children without a craniofacial disorder. Use of a control group for such comparisons is critical but has been rarely undertaken in previous research on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the study's design is limited in its ability to elucidate the mechanisms by which SSC or factors associated with SSC (e.g., surgery and anesthesia exposure 35 ) have led to the group differences observed here and elsewhere. 4,6,9,13,15,23,34,41,48 The etiology of the neurodevelopmental consequences and correlates of SSC remains unclear, with some hypotheses focusing on the effects of the fused suture on brain development [1][2][3]47,49 and others emphasizing preexisting neuropathology that may affect both brain and cranium. 5,19 These studies provide some evidence that changes in brain morphology present prior to surgery persist after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although an isolated single cranial suture closure usually causes only cosmetic deformity, 1 poor gross motor function and learning difficulties resulting from even a single suture synostosis have been reported. [4][5][6][7] Multiple suture synostosis, usually syndromic, has been associated with several complications, such as increased intracranial pressure, headaches, and delayed neurodevelopment. 8 The initial imaging study for infants with suspicion of this condition is generally 4-view radiography [9][10][11][12][13] followed by computed tomography (CT) in cases of positive or equivocal findings at radiography.…”
mentioning
confidence: 99%